The Authenticity of Freelance Videography in Digital Content @Alphaworks.Id - Muhammad Zainal Muttaqin; Siti Khumayah; Aghnia Dian Lestari (Interaction Communication Studies Journal, 2026)
The rapid development of new media and the dominance of digital platform algorithms have transformed how creators construct and perform authenticity in digital content production. In freelance videography, authenticity is no longer understood as spontaneous self-expression but as a strategically constructed performative practice. This study aims to analyze how authenticity is constructed and performed on the Instagram account @alphaworks.id amid algorithmic and commercial pressures. This research employed a qualitative descriptive-analytical approach using in-depth interviews, digital content observation, and literature review. Data were analyzed through thematic analysis using Authenticity as Performativity as the primary analytical framework, supported by new media theory to explain the structural dynamics of digital platforms. The findings reveal that authenticity is constructed through the flexibility of visual and narrative styles, consistency in professional values, transparency in the creative process, and strategic relationship management with audiences and clients. Authenticity also functions as symbolic and economic capital produced through content strategies, performative practices, and selective commercial collaborations. This study concludes that authenticity in social media ecosystems is contextual, dynamic, and continuously negotiated within algorithmic and commercial structures. The findings challenge essentialist perspectives that regard authenticity as an inherent personal trait and demonstrate that authenticity in digital creative practices is a consciously managed performance shaped by platform logic, market demands, and professional identity. These findings also imply that digital creators need to balance professional identity, algorithmic demands, and commercial interests to maintain credibility in digital spaces.